Thrombocytosis in Patients with Pancreatic Cancer Treated with Gemcitabine - Świeboda-Sadlej, Anna; Kraj, Leszek; Krawczyk, Joanna; Nita, Ewa; Dwilewicz-Trojaczek, Jadwiga (Contemporary Oncology/Współczesna Onkologia, 2012)
Gemcitabine is a cytostatic drug from the pyrimidine antimetabolite group. It is used in treatment of some neoplasms, among them inoperable pancreatic cancer. The most common undesirable effects of gemcitabine include pancytopenia, with thrombocytopenia associated with gemcitabine’s myelosuppressive activity. This study contains a description of six cases of patients with pancreatic cancer treated with gemcitabine, who – contrary to expectations – showed increased levels of thrombocytes. The number of thrombocytes ranged from 424 to 1059 x 109 (mean 470 x 109). It was highest during the 2 nd and 3 rd chemotherapy cycles and it normalized after completion of treatment. One patient suffered from a cardiac infarction on the 15 th day of the 3 rd cycle of treatment, despite a normal level of thrombocytes on the day; however, the patient indicated thrombocytosis on the 1 st day of the cycle. No thromboembolic complications were observed in the remaining patients. These patients were not subjected to any antithrombotic prophylaxis. The mechanism by which thrombocytosis occurs after administration of gemcitabine and the clinical significance of this fact remain unknown.